Heat stress induces ferroptosis-like cell death in plants - Distefano, Ayelen Mariana (2017)
In plants, regulated cell death (RCD) plays critical roles during development and is essential for plant-specifi responses to abiotic and biotic stresses. Ferroptosis is an iron-dependent, oxidative, nonapoptotic form of cell death recently described in animal cells. In animal cells, this process can be triggered by depletion of glutathione (GSH) and accumulation of lipid reactive oxygen species (ROS). We investigated whether a similar process could be relevant to cell death in plants. Remarkably, heat shock (HS)-induced RCD, but not reproductive or vascular development, was found to involve a ferroptosis-like cell death process. In root cells, HS triggered an iron-dependent cell death pathway that was characterized by depletion of GSH and ascorbic acid and accumulation of cytosolic and lipid ROS. These results suggest a physiological role for this lethal pathway in response to heat stress in Arabidopsis thaliana. The similarity of ferroptosis in animal cells and ferroptosis-like death in plants suggests that oxidative, iron-dependent cell death programs may be evolutionarily ancient.